Simulation of Helical-Baffle Inlet Structure Cyclone Separator - Guohua Li; Jie Gong; Zijuan Wang; Ran Liu (Separations)
In developing spacecraft dust environment testing equipment, cyclone separators serve as critical particulate separation devices. To optimize cyclone performance, this study investigates the impact of inlet configurations on internal flow fields. We propose a novel helical-baffle inlet design and comparatively analyze it against volute baffle inlets and conventional single-channel inlets using Eulerian–Lagrangian multiphase simulations. Three-dimensional streamline visualization reveals internal flow patterns, while the Q-criterion identifies vortical structures. Results demonstrate that both volute and helical configurations effectively eliminate inlet gas funneling effects. The flow-splitting baffles mitigate flow field asymmetry, with the helical-baffle design exhibiting optimal performance: it maintains vortex stability, enhances fluid dynamic equilibrium, reduces pressure drop and improves separation efficiency to 95.92% for 4 μm particles.